"War, what is it good for?": The industrial revolution! - Stephen D. Billington (Queen's University Centre for Economic History (QUCEH), 2018)
Did the French Revolutionary and Napoleonic wars contribute to the Industrial Revolution? Recent scholarship argues warfare was an important factor in explaining Britain's industrialisation, by encouraging the invention and diffusion of key technologies with military applications. I re-examine this hypothesis by analysing the patenting of military inventions and inventions considered to be economically valuable during the Industrial Revolution. I find war led to a permanent increase in the rate of military and valuable patenting. War likely created a demand for superior military technologies, while increased wartime production led to demands for more valuable technologies, which both stimulated the Industrial Revolution.
Keywords: N43; N74; O31; 330; Industrial Revolution; Patents; War